Physical Capacity and Energy Expenditure of Cavers - Pinna, Virginia; Magnani, Sara; Sainas, Gianmarco; Ghiani, Giovanna; Vanni, Samuele; Olla, Sergio; Marini, Elisabetta; Curreli, Nicoletta; Cabras, Stefano; Farinatti, Paulo; Antoni, Giorgia; Tocco, Filippo; et al. (Frontiers in Physiology, 2017)
CCaves are an extreme environment for humans because of the high humidity, mud, darkness, and slippery conditions. Explorations can last many hours or even days, and require extensive climbing and ropework. Very little is known about the physical capacity of cavers and their energy expenditure (EE) during caving. The physical capacity of 17 (7 females) expert cavers (age 43.9±7.3 yrs) was assessed during an incremental cycle-ergometer test (IET) with gas exchange analysis. Moreover, a wearable metabolic band (Armband Fit Core) was used to estimate their EE during caving. In terms of physical capacity, the IET showed that cavers had a maximum oxygen uptake (VO2max) of 2248.7±657.8 ml•min-1 (i.e. 32.4±6.4 ml·kg-1·min-1), while anaerobic threshold (AT) occurred on average at 74.5 % of VO2max. Results from caving sessions provided an average time spent in cave of 9.4±1.2 hours while the average EE was 268.8±54.8 kcal·h-1, which corresponded to about 40% of VO2max measured during IET. A mean distance of 10.6±2.2 km was covered by subjects. Data from the present investigation provide evidence that cavers have a level of aerobic physical capacity only slightly higher than that of sedentary people, thereby suggesting that a high aerobic fitness is not needed by cavers. Moreover, during caving the EE was on average well below the level of AT. However, in absolute terms, the total EE was elevated (i.e. 2672.3±576 kcal in total) due to the long time spent in caving.